The Development Decade in the Balance - Woods, George D. (Council on Foreign Relations, Inc., 2019)
George D. Woods, President of the World Bank Group, wrote about the crude arithmetic associated with the aim of the Development Decade, which was for the underdeveloped countries as a group to reach a yearly rate of economic growth of five percent. Trends show there will be inadequate improvement in living standards. He highlighted the birth of IFC and IDA, to make development finance available on special terms to countries too poor to borrow at conventional rates of interest and repayment. He mentions the commodity problem and the necessity for a continuing and adequate flows of capital to the developing countries. He wrote of the two initiatives in which the World Bank was joining which could help the developing countries. He suggested more aid to be made available to the developing countries, and on better terms, for a marked change of outlook on the part of the donor countries. He concluded that, from every point of view, it was time for the capital exporting countries to come to a major and irrevocable decision about development assistance to developing countries.